2017
DOI: 10.3988/jcn.2017.13.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia: Review and Update

Abstract: Praxis, the ability to perform skilled or learned movements is essential for daily living. Inability to perform such praxis movements is defined as apraxia. Apraxia can be further classified into subtypes such as ideomotor, ideational and limb-kinetic apraxia. Relevant brain regions have been found to include the motor, premotor, temporal and parietal cortices. Apraxia is found in a variety of highly prevalent neurological disorders including dementia, stroke and Parkinsonism. Furthermore, apraxia has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 74 publications
0
32
0
5
Order By: Relevance
“…[ 17 , 18 ] A recent review suggested that rehabilitative training alone would be insufficient for a sustained benefit. [ 19 ] However, our patient showed significant recovery from apraxia 3 months after completion of our intervention. More studies and large-scale clinical trials are needed to determine the therapeutic efficacy and its mechanism in VR application for apraxia.…”
Section: Discussionmentioning
confidence: 80%
“…[ 17 , 18 ] A recent review suggested that rehabilitative training alone would be insufficient for a sustained benefit. [ 19 ] However, our patient showed significant recovery from apraxia 3 months after completion of our intervention. More studies and large-scale clinical trials are needed to determine the therapeutic efficacy and its mechanism in VR application for apraxia.…”
Section: Discussionmentioning
confidence: 80%
“…Apraxia has been defined as the inability to carry out learned skilled motor acts despite the motor and sensory systems being intact with respect to coordination, comprehension and co-operation (Gross and Grossman, 2008;Heilman and Valenstein, 2003). Apraxia is seen in various neurological disorders, including stroke and neurodegenerative disorders, such as Alzheimer's disease, Parkinson's disease and atypical Parkinsonism, the latter of which includes corticobasal syndrome, multiple system atrophy and progressive supranuclear palsy (Park, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in praxis functions can have obstructive effects on the activities of daily living and can significantly impair the patients' ability to live autonomously (Dovern et al, 2012; Foundas et al, 1995; Hanna–Pladdy et al, 2003). Apraxia occurs in a variety of neurological diseases including stroke, dementia, and movement disorders (Park, 2017; Zadikoff and Lang, 2005). With a prevalence rate varying between 17 and 64%, a substantial number of patients with Parkinson's disease (PD) suffer from apraxic symptoms (Grossman et al, 1991; Leiguarda et al, 1997; Vanbellingen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%